LA ESTABILIDAD DE LOS SERVIDORES PÚBLICOS FRENTE A LA APLICACIÓN DEL DECRETO EJECUTIVO N° 813 - Tinoco Yazbek, Diego Alexander (2016)
The purpose of the research work is to develop the theme: STABILITY OF PUBLIC SERVANTS IN FRONT OF THE APPLICATION OF THE EXECUTIVE DECREE No. 813, because in Ecuador, following that this decree was issued, it has been bombing the job integrity servers public, knowing this that goes against the rights established in the Constitution and international standards bodies. The basic assumption underlying the theme aims to verify whether the Executive Decree No. 813 referred to the "Cessation of functions by purchasing waiver compensation State institutions may establish mandatory procurement plans waivers with compensation as determined the letter k) of Art. 47 of the LOSEP duly budgeted, under restructuring, optimization or rationalization of the same "violates rights under the Law on Public Service and causes instability of the economy of several Ecuadorian households, as evidenced by the National Institute of Statistics and Census equivalent to 4.5% of the poverty level. This research work has the following objectives, in a general sense: the legal, doctrinal and critical analysis of the Organic Law on Public Service, versus what has Executive Decree No. 813: - Determine the scope of this decree against which to art. 81 of the Organic Law on Public Service; - Analyze and determination of violated rights to the implementation of the Decree; - Need for an amendment to the Organic Law of Public Service, in order to ensure job security for public servants. By the decree sought to regulate the untying of servants and servers through the purchase of waivers with compensation, to replace these items with new people without much experience as the government's decision lack of performance and efficiency in their performance.